Literasi Perencanaan Keuangan Islam dalam Perlindungan Konsumen Muslim - Vina Septiana Permatasari; M. Haris Hidayatulloh (Universitas Islam Negeri (UIN) Madura, 2023)
Various financial problems have emerged along with the rapid development of financial technology. Financial technology developments and financial inclusion acceleration which are not in line with financial literacy would harm society. Aspect of financial literacy that must be owned by the society is financial planning ability. Muslim financial planning is different from conventional financial planning. This study describes financial planning by combining financial planning guidelines from the Indonesian Financial Planning Standard Boards (FPSB) with Islamic finance guidelines. The approach of this study are literature study and content analysis which is strengthened by interviews with financial planning experts and participating in the Associate Wealth Planner Syariah (AWPS) Indonesia. The results shows that financial educators who understand Islamic financial planning are highly needed in protecting Muslim consumers. Therefore FPSB Indonesia formed an Association of Sharia Wealth planners (AWPS). The collaboration of various parties is needed in increasing the protection of Muslim consumers through increasing literacy in Islamic financial planning. A Proper Islamic financial planning is expected to help Muslim individuals or households to increase their welfare. This welfare will implicate social welfare and increase safe financial inclusion for Muslim consumers and society.